2021
DOI: 10.4018/ijthmda.2021070103
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Leadership on the Relationship Between Innovation and Performance

Abstract: Leadership, innovation, and performance are essential factors to achieve the desired sustainable profitability of companies. The relationship between these variables is one of the keys to the organizational success, although their study has proved to be complex. The purpose of this article is to analyse the impact of leadership on the relationship between innovation and performance in the Portuguese hotel sector. To answer to this challenge, a survey was carried out to top and middle managers of four-star and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 95 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…According to Huynh (2021), the dimensions of transformational leadership (intellectual stimulation, inspirational motivation, and individual consideration) have positive and significant influence employee strategic renewal behaviour and venture behaviour directly, and via job satisfaction and commitment to organizational change (affective commitment and normative commitment) thus affecting their orientation towards dynamism and new processes. Leitão (2021) likewise asserts that leadership affects goals, visions, strategy, social environment and employee motivation. Leaders need to be creative not only for survival, but also to compete quickly in an ever-changing world.…”
Section: Regression Analysis For Entrepreneurial Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Huynh (2021), the dimensions of transformational leadership (intellectual stimulation, inspirational motivation, and individual consideration) have positive and significant influence employee strategic renewal behaviour and venture behaviour directly, and via job satisfaction and commitment to organizational change (affective commitment and normative commitment) thus affecting their orientation towards dynamism and new processes. Leitão (2021) likewise asserts that leadership affects goals, visions, strategy, social environment and employee motivation. Leaders need to be creative not only for survival, but also to compete quickly in an ever-changing world.…”
Section: Regression Analysis For Entrepreneurial Leadershipmentioning
confidence: 99%
“…This study's results are a confirmation that a higher level of academic entrepreneurship in these universities will result from a higher level of entrepreneurial behavior among academic leaders. Leitão (2021) likewise asserts that leadership affects goals, visions, strategy, social environment and employee motivation. Leaders need to be creative not only for survival, but also to compete quickly in an ever-changing world and since in the hospitality sector, competitiveness depends on the level of innovation in terms of high-quality and low-cost production of its services, which meet or exceed the customer's need with a certain level of novelty and sophistication, inspirational and directional role of the leader towards innovation cannot be overstated.…”
Section: Entrepreneurial Leadership and Hotel Innovation By 1-3 Star ...mentioning
confidence: 99%
“…Literature Review. Leadership is still an extensively debated topic with various definitions, approaches, views, and methods (Leitão et al, 2021), as it has direct and indirect results to organizations and employees.…”
Section: Introductionmentioning
confidence: 99%
“…The previous research has found out the relationship between innovation and performance, and that enhanced innovation increases performance (Leitão et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation